EVALUATION OF HEPATOTOXIC AND NEPHROTOXIC EFFECTS OF PIROXICAM SULFONATED DERIVATIVES - Ali, Asif; Shaheen, Ghazala; Tariq, Shafiq Ahmad; Ullah, Safi; Sultana, Nuzhat; Khan, Naeem; Shah, Inayat; Halimi, Syed Muhammad Ashad; Saeed, Muhammad; Habib, Syed Hamid (Pakistan Journal of Physiology, 2017)
Background: Pain management requires new pharmacotherapy with good efficacy and less side effects. Piroxicam is used routinely in clinical practice but it is associated with side effects. To minimize the chances of adverse effects, sulfonated piroxicam derivatives (SPD) have been introduced. We sought to find hepatotoxic and nephrotoxic effects of SPD in Albino rats. Methods: An experimental study on SPD was carried out at the Institute of Basic Medical Sciences, Khyber Medical University, Peshawar. Healthy 24 albino rats were divided into 5 groups. One control group and four experimental groups (compound I and II, each with a dose of 10mg/kg and 20mg/kg) received treatment for 7 days. Liver function tests (LFTs), renal function tests (RFTs) and histology of liver and kidney specimens was performed after culling rats. The difference between median values of samples was assessed using Kruskal-Wallis test with post-hoc (for LFTs and RFTs). SPSS-21 was used for all statistical analysis and p≤0.05 was considered statistically significant. Results: The alanine aminotransferase (ALT) values were significantly high in the 20 mg/Kg group than control for both compounds (p=0.03, p=0.001 respectively). The aspartate aminotransferase (AST) values were significantly high in the 10 mg/Kg and 20 mg/Kg group than control for compounds II (p=0.01, p=0.0001 respectively). The alkaline phosphatase (ALP) values were significantly high in the 20 mg/Kg group than control for compounds II (p=0.002). The blood urea values were significantly high in the 20 mg/Kg group than control for compounds II (p=0.008). The mean final score of liver injury in all experimental groups (mean range 5–7) was less suggesting that the damage in liver was less pronounced. Renal injury was more pronounced in the 20 mg/Kg dose for both compound I and compound II (mean score 7) compared to 10 mg/Kg dose (mean score 4). Conclusion: Piroxicam sulfonated derivatives can cause focal changes in liver and kidney which might be reversible. The changes are less pronounced for compound I with a low dose. Pak J Physiol 2017;13(4):18–22